On the optimal degree of fluctuations in practice for motor learning - Hossner, E.-J.; Käch, B.; Enz, J. (Human Movement Science, 2016)
In human movement science, it is widely accepted that random practice generally enhances complex motor-skill learning compared to repetitive practice. In two experiments, a particular variability-related concept is put to empirical test, namely the concept of differencial learning (DL), which assumes (i) that learners should not be distracted from task-space exploration by corrections, and (ii) that learning is facilitated by large inter-trial fluctuations. In both experiments, the advantage of DL over repetitive learning was not statistically significant. Moreover, learning was more pronounced when participants either received corrections in addition to DL (Exp. 1) or practiced in an order in which differences between consecutive trials were relatively small (Exp. 2). These findings suggest that the positive DL effects reported in literature cannot be attributed to the reduction of feedback or to the increase of inter-trial fluctuations. These results are discussed in the light of the structural-learning approach and the two-state model of motor learning in which structure-related learning effects are distinguished from the capability to adapt to current changes.